Developing student outcomes in real-world learning experiences: The case of solar decathlon in Latin America (2016)
Engineering students face a future in which professional skills (e.g., working in multidisciplinary teams, ethics, and communicate effectively) will be equally important as hard skills (e.g., design systems and solve technical problems). However, the development and assessment of these skills by the time of graduation is still a challenge for higher education institutions. In ABET terms, the student outcomes describe what students are expected to know and be able to do by the end of their undergraduate program. Thus, an ABET outcome might include a set of several skills. One strategy for developing these professional and hard skills is to expose engineering students to hands-on, real-world experiences. In this paper, a full analysis of how a multidisciplinary competition like the Solar Decathlon can contribute to the simultaneous development of various student outcomes is presented. The Solar Decathlon (SD) competition is an initiative of the U.S Department of Energy that challenges students to design, build, and operate sustainable, solar-powered, and affordable houses. A survey of all members of the team composed of students from the Universidad Icesi and the Pontificia Universidad Javeriana Cali participating in the Solar Decathlon for Latin America & Caribbean 2015 was carried out three times during the competition: at the beginning stage, in the middle of the project, and at the end of the competition. The goal was to analyze the attainment of student outcomes and their development over time. This team was comprised of 40 students from eight professional disciplines (including four industrial engineering students) for more than a year. Furthermore, this study presents how the interdisciplinary composition of the team evolved throughout the development of the project in order to fulfill the requirements of the competition. The role and participation of industrial engineers in this type of project was also examined as well as the primary personal and professional challenges experienced by the participants. Findings suggest that working and communicating effectively with students from other disciplines (i.e., multidisciplinary teaming) were among the main professional challenges students faced during the project. Likewise, respect for other people's perspectives and different paces of work between disciplines were the most common personal challenges. Lessons learned and recommendations for future competitors (institutions and students) are also presented.